International transfer of climate technologies: Which factors influence the firm's choice of transfer channel? - Jan Peuckert; Cleo Schmid; Carsten Gandenberger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
Based on a survey among German climate technology companies, we analyse how characteristics of the technology and organization-specific resources influence the channel chosen for transferring climate technologies to other countries. We employ a multi-step method that combines factor analysis and hierarchical logistic regression. Our results suggest that organizations tend to choose hierarchical modes of transfer with increasing relevance of firm-internal capabilities. The most significant empirical link exists between the complexity of the relevant technology and the observed mode of transfer. A high degree of technological complexity tends to increase the likelihood of internal transfers, which is consistent with the assumption that the transfer of tacit knowledge requires a higher amount of personal communication between donor and recipient.
urn:nbn:de:0011-n-3476764
Keywords: 330; International Technology Transfer; Climate Technology; Transfer Channel; Tacit Knowledge; Transaction Costs Economics